50.6k views
5 votes
What is the solution for this proportion?

What is the solution for this proportion?-example-1
User Gligoran
by
5.3k points

1 Answer

4 votes

Answer:

n = -3

Explanation:

Cross multiply. We get:

(n - 6)(3n + 1) = 3n(n - 5), or

3n² + n - 18n - 6 = 3n² - 15n

Simpify by combining like terms. 3n² on the left is the same as 3n² on the right, so we cancel these terms:

n - 18n - 6 = - 15n.

Continuing to combine like terms, we get:

-2n = 6, so that n = -3.

Note that there is no problem subbing -3 for n in the given proportion; both fractions will be defined. Thus, n = -3 is the solution desired.

User Tsahi Asher
by
5.5k points